Direct Access to Acylated Azobenzenes and Amide Compounds by Reaction of Azoarenes with Benzylic Ethers as Acyl Equivalents - Hong, Gang; Aruma, Alfred Njasotapher; Zhu, Xiaoyan; Wu, Shengying; Wang, Limin (Synthesis, 2016)
Described herein is the use of N=N double bond of azobenzene as both directing group and radical acceptor in one-reaction protocol for the first time. An efficient pathway for the Pd-catalyzed regiospecific ortho-acylation of azoarenes using benzylic ethers as acyl equivalents has been achieved. In the absence of palladium catalyst, amide compounds were formed by the reaction of azoarenes with benzylic ethers under certain conditions. Various mono-acylazobenzene and amide compounds were obtained in good yields (35 examples). The mono-acylated products and amide products could be easily controlled by palladium catalyst.
Keywords: azobenzenes; synthetic methods; radical reaction; directing group; benzylic ether; amide compounds